2017
DOI: 10.1002/ardp.201600304
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Synthesis of bi‐Aryl Pyrimidine Heterocycles: Potential New Drug Candidates to Treat Alzheimer's Disease

Abstract: A series of 13 novel pyrimidine-based sulfonamides 6a-m were synthesized in short periods of time under microwave conditions in good to excellent yield (54-86%). The chemical structures of these heterocycles consist of a central pyrimidine ring having a phenyl group and pyrimidine groups with sulfonamide motifs. The enzyme inhibitory potential of these compounds was investigated against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) because these enzymes play a crucial role in the treatment of Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Additionally, the docked complex of BChE with 6j (BChE-6j) showed that the hydrophobic patch residue Tyr128 and the catalytic triad residue Ser198 were involved in intramolecular hydrogen bonding ( Fig. 25) [149].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Additionally, the docked complex of BChE with 6j (BChE-6j) showed that the hydrophobic patch residue Tyr128 and the catalytic triad residue Ser198 were involved in intramolecular hydrogen bonding ( Fig. 25) [149].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Under MW irradiation, the reaction time is reduced about five folds and the yields were slightly higher. Rehman et al [65] synthesized new pyrimidines (83a-m) that were decorated with pyridine and sulfonamide moieties of potential interest in Alzheimer's disease. The syntheses were carried out under conventional TH and MW irradiation.…”
Section: Six Membered Ring Azaheterocycles With Two and More Heteroatomsmentioning
confidence: 99%
“…By comparison with reaction under classical TH, under MW irradiation the yields were higher (with about 20-25%) and the reaction time substantially decreased, from about 800 to 15 min. Rehman et al [65] synthesized new pyrimidines (83a-m) that were decorated with pyridine and sulfonamide moieties of potential interest in Alzheimer's disease. The syntheses were carried out under conventional TH and MW irradiation.…”
Section: Six Membered Ring Azaheterocycles With Two and More Heteroatomsmentioning
confidence: 99%
“…The increasing mortality rate, complexities in disease and the limited option of drugs for the curing of AD, demand new and more effective pharmacological products. Keeping these factors in view researchers is aiming to develop new potential drugs …”
Section: Introductionmentioning
confidence: 99%